Reduction of skeletal anomalies in meagre (Argyrosomus regius, Asso, 1801) through early introduction of inert diet - Martins, Gil (2020)
The consolidation of meagre (Argyrosomus regius) in aquaculture requires an understanding and optimization of larval rearing and nutritional conditions. The aim of this study was to analyse the effects of an early introduction of inert diets during larval rearing, on growth performance, digestive enzymes activity and development of skeletal anomalies. This study evaluated the effects of three different timings for the introduction of inert diet during larval rearing: a control group (CTRL) where inert diet was initiated at 14 days after hatching (DAH) and two treatment groups that had an earlier introduction of inert diet at 8 DAH (T1) and 11 DAH (T2). Meagre larvae exhibited similar pancreatic and intestinal enzymatic activities among the different dietary treatments. No differences in the overall prevalence of anomalies were observed between treatments at 25 or 50 DAH, however, a significant reduction was observed in all groups with the transition from larval to juvenile stage. The precocious introduction of inert diet shifted the distribution of vertebral anomalies to a more anterior vertebral column region. Altogether, this study shows that earlier introduction of inert diets in meagre hatcheries can be beneficial for meagre production in aquaculture.